The psychosocial implications of sport specialization in pediatric athletes - Brenner, J. S.; LaBotz, M.; Sugimoto, D.; Stracciolini, A. (Journal of Athletic Training, 2019)
Data on the psychosocial implications of sport specialization in pediatric athletes are lacking. Sport specialization often requires increased training hours and may predispose young athletes to social isolation, poor academic performance, increased anxiety, greater stress, inadequate sleep, decreased family time, and burnout. Sport specialization frequently introduces multiple stressors that could be expected to adversely affect mental health and function in young athletes and may increase the risk for burnout. This may be confounded by altered sleep duration and quality, increased drive for elite status, and perfectionistic personality types. The signs and symptoms of burnout in young athletes can be difficult to detect. It is important to be aware of the possible diagnosis of burnout in young athletes who display vague symptoms and a decrease in academic performance. The purpose of this review was to survey the available literature on sport specialization in young athletes and its association with mental health, sleep, the drive for success in sport, and burnout.